2015
DOI: 10.3389/fnins.2015.00291
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study into the effects of music therapy on different areas of the brain of individuals with unresponsive wakefulness syndrome

Abstract: The global cerebral network allows music “ to do to us what it does.” While the same music can cause different emotions, the basic emotion of happy and sad songs can, nevertheless, be understood by most people. Consequently, the individual experience of music and its common effect on the human brain is a challenging subject for research. Various activities such as hearing, processing, and performing music provide us with different pictures of cerebral centers in PET. In comparison to these simple acts of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…67 Even if, to date, no double-blind RCT has been conducted to evaluate the clinical effects of music in patients with DOC, neuroimaging has shown higher activation of the auditory network and stronger neurophysiological responses (i.e., increase in P300 response) following music compared to other random sounds (figure 2I). [68][69][70][71] A recent uncontrolled ABAB protocol tested the effects of a multi-sensory stimulation program including auditory, visual, tactile, olfactory, and gustatory stimuli (20 minutes per session applied 3 days per week for 4 weeks). 72 Higher CRS-R total scores were observed during the treatments periods (B) compared to baselines (A) in MCS but not in UWS patients groups.…”
Section: Sensory Stimulation Programsmentioning
confidence: 99%
“…67 Even if, to date, no double-blind RCT has been conducted to evaluate the clinical effects of music in patients with DOC, neuroimaging has shown higher activation of the auditory network and stronger neurophysiological responses (i.e., increase in P300 response) following music compared to other random sounds (figure 2I). [68][69][70][71] A recent uncontrolled ABAB protocol tested the effects of a multi-sensory stimulation program including auditory, visual, tactile, olfactory, and gustatory stimuli (20 minutes per session applied 3 days per week for 4 weeks). 72 Higher CRS-R total scores were observed during the treatments periods (B) compared to baselines (A) in MCS but not in UWS patients groups.…”
Section: Sensory Stimulation Programsmentioning
confidence: 99%
“…But only recently brain imaging methods like fMRI, PET, EEG have been introduced in the research about music therapy in DOCs. A study employing PET as a reliable measure to better understand the relationship between music therapy and neuroscience before, during and after music therapy (Steinhoff et al, 2015) scanned the metabolism of the brain three times with PET during resting state, first exposure to music therapy (MT), and last exposure to MT. The final result showed that in the three areas analyzed in this study, the frontal areas, the hippocampus and the cerebellum, patients in music therapy showed higher brain activity than the control group (Steinhoff et al, 2015).…”
Section: Auditory Stimulation For Treatment Measurementioning
confidence: 99%
“…A study employing PET as a reliable measure to better understand the relationship between music therapy and neuroscience before, during and after music therapy (Steinhoff et al, 2015) scanned the metabolism of the brain three times with PET during resting state, first exposure to music therapy (MT), and last exposure to MT. The final result showed that in the three areas analyzed in this study, the frontal areas, the hippocampus and the cerebellum, patients in music therapy showed higher brain activity than the control group (Steinhoff et al, 2015). The same conclusion was carried out in three other EEG studies (O’Kelly et al, 2013; Sun and Chen, 2015; Park et al, 2016), one of which aimed at evaluating the effects of a preferred music intervention on the reduction of agitation in TBI patients, showing that patients in music therapy also had better behavioral or neurophysiological indexes than the control group, and that a significantly greater reduction in agitation was observed in the patients listening to the preferred music (Park et al, 2016).…”
Section: Auditory Stimulation For Treatment Measurementioning
confidence: 99%
“…However, there is evidence to suggest that patients with DOC may not exhibit detectable cerebral responses at rest, or upon the application of simple brain stimulation paradigms, as such patients cannot cross the threshold for plasticity modifications; thus, they exhibit no detectable response [ 6 ]. Emotion is a key aspect involved in individuals’ experiences of their external environment and can persist in subjects with severe brain damage [ 7 ]. Emotional stimuli are likely to preferentially capture an individual’s attention and be processed by integration of primitive neural processes.…”
Section: Introductionmentioning
confidence: 99%